Mechanical Properties of GF/pCBT Composites and Their Fusion-Bonded Joints: Influence of Process Parameters - Zhang, L.; Wang, Z.Q.; Zhou, L.M. (Проблемы прочности, 2015)
High melting viscosity of thermoplastic composites gives no way of using substantial volume fractions of reinforcing agents. This problem can be solved by in-situ polymerization of an extremely low-viscosity cyclic butylene terephthalate (CBT) resin. Continuous glass fiber-reinforced poly(cyclic butylene terephthalate) (GF/ðCBT) composites with high fiber fractions were manufactured, and the mechanical properties as a function of the catalyst mass fraction and fiber filling ratio were studied. The longitudinal tensile strength of the composites was enhanced by increasing the fiber volume fraction, and the influence of the fiber fraction on the bending strength of high fiber filling-ratio composites was evaluated. Furthermore, the mechanical properties and failure modes of GF/ðCBT fusion-bonded joints with different number of bonding areas of different lengths were investigated. It was found that high-strength composite materials can be obtained, which are applicable for fusion-bonded structures. Высокая вязкость плавления термопластических композиционных материалов не позволяет использовать значительные объемные долевые концентрации армирующих наполнителей. Эта проблема может быть решена путем in-situ полимеризации циклобутилентерефталатной смолы с чрезвычайно низкой вязкостью. Были изготовлены поли(циклобутилентерефталатные) композиционные материалы, армированные непрерывным стекловолокном (CF/pCBT) с высоким его содержанием, изучены механические свойства с учетом весовой доли катализатора и степени наполнения волокном. Предел прочности композиционных материалов при растяжении в продольном направлении возрос за счет увеличения объемной доли концентрации волокна, изучено влияние объемной доли волокна на прочность при изгибе для композиционных материалов с высокой степенью наполнения волокном. Кроме того, исследованы механические свойства и режимы разрушения GF/pCBT сваренных плавлением соединений с различным количеством зон связывания разной длины. Установлено, что можно получать высокопрочные композиционные материалы, пригодные для сваренных плавлением конструкций.